A crustacean vitellogenin-derived peptide as an oocyte-specific delivery vehicle for gene silencing - Cohen, Shany; Hasan, Mahde; Frishman, Noa; Khalaila, Isam (Frontiers in Marine Science, 2023)
Gene silencing by dsRNA is well documented in crustaceans, but RNA interference (RNAi) in developing oocytes is yet to be achieved. The main obstacle to RNAi in the oocytes of oviparous animals derives from their protective layers, including the cytosolic membrane, the vitelline envelope, and a layer of follicular cells. These layers form a barrier preventing the entry of large nonspecific molecules, such as double-stranded RNA (dsRNA). This article describes a sophisticated tool – designated OSDel [oocyte-specific delivery] – for the delivery of dsRNA for gene silencing in the developing oocyte. The methodology exploits the process of receptor-mediated endocytosis (RME) taking place in the crustacean female for internalizing vitellogenin (Vg) (the precursor of the major yolk protein, vitellin) into oocytes. In this process, the extracellular domain of the Vg receptor (VgR) interacts with a distinct amino acid sequence of Vg and internalizes it to form yolk droplets. Here, we tested the premise that a distinct 24 amino-acid peptide derived from Macrobrachium rosenbergii Vg (designated VgP) would interact with VgR to form particles of a size suitable for piggy-backing dsRNA into oocytes via RME. We found that fluorescently labeled VgP had a micromolar affinity for the ligand-binding domain (LBD) of the VgR and could indeed be delivered to and internalized in oocytes. As model system to illustrate the applicability of the OSDel, we injected vitellogenic females with dsRNA encoding the eye development gene PAX6 piggybacked on VgP. Proof that the dsRNA had been successfully internalized into the developing oocytes and had silenced the PAX6 gene was derived from impaired eye development in 87% of the embryos. The ability to manipulate embryos by simple injection into vitellogenic crustacean females may prove to be a powerful high throughput tool for functional genomics investigation in crustacean embryos and for silencing genes relevant to crustacean aquaculture and biotechnology.